Conservative versus operative management of mid-clavicular fractures - Dahal, Saurav; Shrestha, Shriraj; Bhandari, Parash; Bajracharya, Suraj; Bajracharya, Aayush; Maharjan, Basanta (Journal of Chitwan Medical College, 2021)
Background: Mid-clavicle fractures were traditionally managed by non-operative means which led to stiffness and painful shoulder. Surgical treatment on the other hand had the advantage of reducing malunion and allowing early shoulder movements, but also had incidences of infection. This study was carried out with the objectives of comparing functional outcome, fracture union rates, patient satisfaction rates and complications of both treatments. Methods: In this observational study done from October 2020 to September 2021 in the Orthopedics and Emergency department of KIST Medical College Teaching Hospital, Lalitpur, Nepal, 40 patients with mid-clavicle fractures were treated either conservatively or operatively according to their choice. 20 patients in each group were assessed functionally in each follow-up using the Constant and Murley score and union and complications were also assessed. Data collection and entry was done using the statistical package for social science version 22 and analyzed by using statistical tools like mean, frequency and Independent samples t-test. Results: At 6 months, there was no statistical difference in the Constant and Murley score between the two groups, but the scores were statistically better in the operative group at 6 weeks. Mean fracture union time in operative group (12.67 weeks) was statistically better than that in conservative group (14.89 weeks). Complications in operative group were mainly hardware related while stiffness was more common in conservative group. Conclusions: Operative treatment led to earlier fracture union, regain of shoulder function and return to work, but had the disadvantage of high cost and risk of infection as compared to conservative treatment.